2020
DOI: 10.1002/agj2.20253
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance of two pea lines to powdery mildew

Abstract: The GRICAND, Andean Crops Research Group has identified two resistant pea (Pisum sativum L.) lines to powdery mildew (PM) (Erysiphe pisi): ILS6527 (resistance of foliage and pods) and UN6651 (pods only resistance). This study established the inheritance of these two distinct PM‐resistance genotypes. Resistant lines ILS6527 and UN6651 were crossed with two susceptible varieties (Andina and San Isidro) and their respective generations (F1, F2, BCr, and BCs) were evaluated for PM resistance in naturally infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The lines of this group were less susceptible to powdery mildew. Erysiphe pisi (Ep) is the main causal agent of powdery mildew (PM) in peas and is responsible for 25-80% losses in yield worldwide (León et al, 2020;Nisar et al, 2006).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The lines of this group were less susceptible to powdery mildew. Erysiphe pisi (Ep) is the main causal agent of powdery mildew (PM) in peas and is responsible for 25-80% losses in yield worldwide (León et al, 2020;Nisar et al, 2006).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Different PM disease scoring scales have been proposed by different researchers and the scales of 0-4, 0-5, 1-5, 0-9, and 0-10 have been used for scoring the PM disease (Table 1). ≤ 20% = R [35] Where R: Resistant; MR: Moderately Resistant.…”
Section: Pm Disease Scale In Peamentioning
confidence: 99%
“…Studies on the inheritance of PM disease revealed three genes, namely er1, er2 and Er3, conferring resistance to Erysiphe species [22], (Figure 2). An investigation into the genetics of powdery mildew resistance (PMR) has been carried out in the past, which has shown different modes of inheritance including single recessive [35,36], single dominant [9,37] and duplicate recessive gene actions [38,39] (Table 2). Hammarlund [19] was the first to investigate PM resistance in peas and reported cumulative factors for susceptibility.…”
Section: Geneticsmentioning
confidence: 99%
“…Different modes of inheritance i.e. single recessive 12 , 13 , single dominant 14 , 15 and duplicate recessive gene action 16 , 17 have been reported for powdery mildew resistance. The recessive ‘er1’ gene is responsible for resistance to majority of the naturally occurring powdery mildew disease 18 21 and was commonly used in pea breeding for development of PMR cultivars.…”
Section: Introductionmentioning
confidence: 99%